Comparative Efficacy of Haizao Yuhu Decoction Composed of Different Varieties of Glycyrrhiza in Goiter Rats. (16th September 2021) - Chen, Feng; Li, Na; Xiu, Linlin; Liu, Haiyan; Chen, Shaohong; He, Cheng; Fan, Angran; Yu, Xue; Wang, Xin; Ge, Chaoran; Huo, Min; He, Jia; et al.
Abstract : In traditional Chinese medicine, Glycyrrhiza and Sargassum are one pair of the "18 incompatible medicaments, " which in theory cannot be used together. However, since ancient times, many reports have described using compounds containing both Glycyrrhiza and Sargassum to treat diseases. Haizao Yuhu Decoction (HYD), which contains both ingredients, is mainly used to treat goiter. Chinese Pharmacopoeia officially recorded three varieties of Glycyrrhiza : Glycyrrhiza uralensis, Glycyrrhiza inflata, and Glycyrrhiza glabra . These three varieties have certain differences in chemical composition and pharmacological effects. The purpose of the present study was to investigate whether the HYD containing different varieties of Glycyrrhiza and Sargassum had different therapeutic effects in rats with goiter and to elucidate the underlying mechanism of any difference. In this study, propylthiouracil (PTU) was used to replicate the goiter model, then HYDs containing different varieties of Glycyrrhiza were used for treatment for four weeks, and then the relevant indicators were tested. The results demonstrated that HYD had antigoiter effects, alleviated the pathological changes in the thyroid tissue, and restored the abnormal serum levels of hormones related to thyroid function induced by PTU. HYD containing Glycyrrhiza uralensis had the best therapeutic effect in rats with PTU-induced goiter. The antigoiter effect of HYD may function through the hypothalamic-pituitary-thyroid (HPT) axis, inhibit the expression of the Tg and NIS genes, and regulate the synthesis of thyroid hormones, thereby reducing the excessive stimulation of TSH in thyroid cells. In addition, HYD also prevented goiter by promoting thyroid cell apoptosis and inhibiting the ERK/RSK1 pathway of cell proliferation. In conclusion, three types of HYD had different therapeutic effects in rats with goiter, which might be caused by the compatibility of different varieties of Glycyrrhiza and Sargassum .